A scoping review of COVID-19 vaccine hesitancy: refusal rate, associated factors, and strategies to reduce - Bahreini, Rona; Sardareh, Mehran; Arab-Zozani, Morteza (Frontiers in Public Health, 2024)
Objective: To investigate the evidence regarding vaccine hesitancy including refusal rate, associated factors, and potential strategies to reduce it. Methods: This is a scoping review. Three main databases of PubMed, Scopus, and Web of Science were searched from 1 Jan 2020 until 1 Jan 2023. All original studies in the English language that investigated one of our domains (vaccine hesitancy rate, factor associated with vaccine hesitancy, and the ways/interventions to overcome or decrease) among the general population were included in this study. The data charted using tables and figures. Also, a content analysis conducted using the 3C model of vaccine hesitancy (Confidence, Complacency, Convenience) that was previously introduced by WHO. Results: Finally, 184 studies were included in this review. Of these, 165, 181, and 124 studies reported the vaccine hesitancy rate, factors associated, and interventions to reduce or overcome, respectively. Factors affecting the hesitancy rate are categorized into four themes and 18 sub-themes (contextual factors, confidence barriers, complacency barriers, and convenience barriers). Conclusion: Vaccine hesitancy rate and the factor affecting it are different according to different populations, contexts, and data collection tools that need to investigate in specific populations and contexts. The need to conduct studies at the national and international levels regarding the reasons for vaccine refusal, the factors affecting it, and ways to deal with it is still felt. Designing a comprehensive tool will facilitate comparisons between different populations and different locations.